Reconceptualizing object construction: the dynamics of Building Information Modelling in construction design. (22nd September 2016) - Miettinen, Reijo; Paavola, Sami
Abstract: The article discusses the concepts of object and object construction through studying the collaborative use of Building Information Modelling (BIM) in construction design. It suggests that a combined BIM model in design can be regarded as an ideal or special object, as suggested by Ilyenkov in his theory of the ideal. The concepts of intermediary object and artefact help in analysing the cycles of construction of such an object in design. BIM models as modifiable digital artefacts contribute to their capability of functioning as tools of individual design work and collaboration as well as means of objectifying the outcomes of design cycles into intermediary objects. We argue that the uses of combined BIM models give birth to a new modality of spatial thought, perception and collaborative problem solving in construction design.